Developing countries and neglected diseases: challenges and perspectives - Boutayeb Abdesslam (BMC, 2007)
Abstract It is now commonly admitted that the so-called (most) neglected tropical diseases have been given little attention. According to World Health Organization, neglected diseases are hidden diseases as they affect almost exclusively extremely poor populations living in remote areas beyond the reach of health service. The European Parliament recognised that, to our shame, Neglected Diseases have not received the attention they deserve from EU actions. In the Millennium Development Goals they were given very little attention and mentioned just as other disease. Investing in drugs for these diseases is thought to be not marketable or profitable. However, despite their low mortality, neglected diseases are causing severe and permanent disabilities and deformities affecting approximately 1 billion people in the world, yielding more than 20 millions of Disability Adjusted Life Years (56.6 million according to Lancet's revised estimates) and important socio-economic losses. Urgent pragmatic and efficient measures are needed both at international and national levels.